2020
DOI: 10.15694/mep.2020.000203.1
|View full text |Cite
|
Sign up to set email alerts
|

Residency Program Social Media Accounts and Recruitment - A Qualitative Quality Improvement Project

Abstract: Social media use by United States medical residency programs has been gaining traction in medical education over the last few years. However, the degree of influence of residency program social media presence on a U.S. residency applicant's decision to apply to or rank a residency program through the National Resident Matching Program is unknown. Here we present our 2019 post-match quality improvement survey data from newly matched residents to Internal Medicine and Transitional Year residency programs at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
5
8
0
Order By: Relevance
“…The ability of social media to benefit a program by conveying relationships and conversations within the department to recruit applicants has been reported 20 . Our results are consistent with previous qualitative reports that social media is effective in helping a program exhibit its personality and seem more approachable 17 . This may suggest that social media offers insight into a program that is less available on a formal residency website.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ability of social media to benefit a program by conveying relationships and conversations within the department to recruit applicants has been reported 20 . Our results are consistent with previous qualitative reports that social media is effective in helping a program exhibit its personality and seem more approachable 17 . This may suggest that social media offers insight into a program that is less available on a formal residency website.…”
Section: Discussionsupporting
confidence: 93%
“…However, its impact on applicants remains poorly understood. Through studies in internal medicine, anesthesiology, and plastic surgery, it has been suggested that social media can have an impact on applicants and even assist them in deciding where to apply and rank prospective programs 11 , 17 , 18 . Our results demonstrate that social media is increasingly being used by orthopaedic surgery applicants to learn more about programs and that this has had a positive impact in most of the outcomes we studied.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,12 Findings from the present study corroborate previous observations that social media can help a program show its personality and appear more approachable. 10,13 In addition, this study included other common social media platforms such as Facebook and Snapchat. Interestingly, these platforms had relatively fewer applicants accessing these sites.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the switch to virtual interviews, applicants had already been turning to social media to obtain information about programs ( 7 , 8 ). In an article published in September of 2020, Fick et al demonstrated that 41.6% of applicants surveyed were influenced by social media when deciding which programs to apply to ( 8 ).…”
Section: Discussionmentioning
confidence: 99%